Enhancing the health potential of processed meat: the effect of chitosan or carboxymethyl cellulose enrichment on inherent microstructure, water mobility and oxidation in a meat-based food matrix. Issue 7 (6th July 2018) - Han, Minyi; Clausen, Mathias P.; Christensen, Morten; Vossen, Els; Van Hecke, Thomas; Bertram, Hanne Christine
Abstract : The addition of dietary fibers can alleviate the deteriorated textural properties and water binding capacity (WBC) that may occur when the fat content is lowered directly in the formulas of comminuted meat products. Abstract : The addition of dietary fibers can alleviate the deteriorated textural properties and water binding capacity (WBC) that may occur when the fat content is lowered directly in the formulas of comminuted meat products. This study investigated the effects of the addition of chitosan or carboxymethyl cellulose (CMC) (2% w/w) to a model meat product. Both dietary fibers improved the water-binding capacity (WBC), while chitosan addition resulted in a firmer texture, CMC lowered the hardness. Chitosan addition resulted in a 2-fold reduction of lipid oxidation products, whereas CMC had no significant effect on oxidation. The effect of chitosan addition on lipid oxidation was evident both in the meat system and after simulated in vitro gastrointestinal digestion. Low-field nuclear magnetic resonance (NMR) relaxometry revealed that the fibers impacted the intrinsic water differently; the addition of chitosan resulted in a faster T 2 relaxation time corresponding to water entrapped in a more dense pore network. Coherent anti-Stokes Raman scattering (CARS) microscopy was for the first time applied in a meat product to study the microstructure, which revealed that the two fibers exerted different effects on the size and entrapment of fat droplets in the protein network, which probably explain the mechanisms by which chitosan reduced lipid oxidation in the system.